2016
DOI: 10.2147/opth.s116743
|View full text |Cite
|
Sign up to set email alerts
|

Central corneal thickness of Iraqi population in relation to age, gender, refractive errors, and corneal curvature: a hospital-based cross-sectional study

Abstract: BackgroundCentral corneal thickness (CCT) is an important indicator of corneal status. Its measurement provides valid information about corneal physiological condition and possible changes associated with diseases, traumas, and hypoxia. It is an integral part for interpretation of intraocular pressure and glaucoma patient management and in prerefractive procedure assessment.ObjectiveThe aim of this study is to determine the mean CCT among a normal Iraqi population and to correlate between CCT and age, gender, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 37 publications
4
28
2
1
Order By: Relevance
“…AL strongly affects the refraction status because its elongation leads to the progression of myopia. CCT in our study was 539 ± 36.74 µm, which was higher than that of Chang et al, (533 ± 29 µm) [15] and tied with those of Kadhim and Farhood [16] (543.95 ± 32.58 µm) and Kawesch (548 ± 33 µm) [17]. CCT plays a key role in the surgical plan or refractive surgeons.…”
Section: Discussionsupporting
confidence: 39%
“…AL strongly affects the refraction status because its elongation leads to the progression of myopia. CCT in our study was 539 ± 36.74 µm, which was higher than that of Chang et al, (533 ± 29 µm) [15] and tied with those of Kadhim and Farhood [16] (543.95 ± 32.58 µm) and Kawesch (548 ± 33 µm) [17]. CCT plays a key role in the surgical plan or refractive surgeons.…”
Section: Discussionsupporting
confidence: 39%
“…A similar research was conducted in China and no relationship was found between the SE and the CCT, as in our study 29. Conversely, a study in Iraqi people found a statistically significant positive correlation with the same variables 15. As shown in Table 4, the thickest corneas appear at the end of the two refractive spectrums: severe myopia and moderate hypermetropia.…”
Section: Discussionmentioning
confidence: 87%
“…Pada studinya dilaporkan pada mata miopia terjadi penipisan ketebalan kornea sentral sekitar 539,5 µm dibandingkan mata normal yaitu 550,47µm. 15 Penelitian yang serupa juga dilakukan oleh Ks dan Anuradha tahun 2019, dalam penelitiannya dikemukakan bahwa peningkatan derajat miopia akan menyebabkan penurunan ketebalan kornea sentral. Rata-rata ketebalan kornea sentral pada >3,5 D adalah 535,5 µm dan pada mata miopia <1,25 D ialah 558,33 µm.…”
Section: Pembahasanunclassified